2015
DOI: 10.14238/pi55.2.2015.06
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative NS1 antigen and the severity of dengue virus infections

Abstract: Background Dengue infection is one of the main cause of morbidity and mortality in children in Indonesia. Since it is known that earlier treatment and supportive therapies can decreased case fatality rate from dengue hemorrhagic fever (DHF), identification of children who have risks to develop to DHF must be quickly identified, mainly in areas of endemic. Objective To find a correlation between increased quantitative secreted nonstructural protein-1 (sNS1) with clinical course of severe dengue infections. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The association of NS1 antigen with disease severity in dengue virus infection have been commonly studied, however the results are contradictory and inconclusive. Several studies reported that the presence of circulating NS1 antigen was associated with a higher risk of developing severe manifestations and the serum NS1 levels were higher in patients with SD than those with mild dengue fever [16,17,43]. On the other hand, there is a paper showing that low NS1 antigen level instead was associated with more severe form of dengue [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of NS1 antigen with disease severity in dengue virus infection have been commonly studied, however the results are contradictory and inconclusive. Several studies reported that the presence of circulating NS1 antigen was associated with a higher risk of developing severe manifestations and the serum NS1 levels were higher in patients with SD than those with mild dengue fever [16,17,43]. On the other hand, there is a paper showing that low NS1 antigen level instead was associated with more severe form of dengue [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, NS1-induced vascular leakage was discussed only in recent years and the contribution of NS1 to vascular leakage as well as the mechanism of pathogenesis remains controversial. Several studies reported that the level of NS1 was higher in patients with severe dengue (SD) [16,17] and it appears to contribute to disease severity by inducing IL-10 production by monocytes [18], activating immune cells via toll-like receptor 4 [19] or disrupting the endothelial glycocalyx components leading to increased vascular permeability [20]. On the other hand, studies also showed that low level of NS1 can also be associated with more severe manifestations [21] and the NS1 positivity did not correlate with severe pathologies [22].…”
Section: Introductionmentioning
confidence: 99%